PEMANFAATAN SALVINIA MOLESTA D.S. MITCHELL, AKUMULATOR MERKURI DI SAWAH TERCEMAR LIMBAH PENAMBANGAN EMAS - Hidayati, Nuril; Syarif, Fauzia; Juhaeti, Titi (Jurnal Teknologi Lingkungan, 2009)
Mercury is one of important contaminants in mine lands. One approach to remediaterisks from this metal pollutant is phytoextraction using hyperaccumulator plants. Theseremarkable plant species accumulate appreciable high concentrations of metals thando normal plants when the normal plants suffer yield reduction from metal phytotoxicity.Some plant species growing in gold mine contaminated areas indicated high toleranceand potentially effective in accumulating mercury in their roots and above groundportions. Salvinia molesta is one of them. This plant could be utilized as hyperaccumulatorfor cleaning up mercury contaminated sites. This research aim to study phytoextractionof mercury by Salvinia molesta and the effectiveness of mercury degradator bacteria onplant tolerance and mercury phytoextraction. In this study Salvinia molesta was grown inmercury contaminated liquid gold mine waste, added with Mercury (II) Chloride (HgCl2)0 ppm Hg, 10 ppm Hg, 30 ppm Hg and 50 ppm Hg. Mercury degradator bacteria wasapplied in the media. The results showed that Salvinia molesta was able to survive evenin media with high level of mercury concentration (50 ppm), although the number ofplant survival tend to decrease with the increase of mercury concentration. Variables ofsurface coverage and live plants decreased with the increase of mercury concentrationin the media. There was a close correlation between plant growth variables and mercuryconcentration in the media. The effects of mercury toxicity on plants seems to decreasein bacteria treated plants. It was indicated by the higher percentage of surface coverageand plant survival in bacteria treated plants than that of untreated plants up to 30 ppm Hg.Recovery from toxicity was shown in bacteria treated plants up to 30 ppm Hg. Mercuryaccumulation in plants tent to increase with the increase of mercury concentration inmedia. It can be concluded that plant performance was better and mercury concentrationdecreased in bacteria treated plants.